The causative infix in Spanish verbs - Ladislao Imaz Fernández de Casadevante (Estudios de Lingüística, 2005)
In accordance with studies of modern Linguistics Typology regarding the infix, it has been recognized in many ancient and existing languages as an important derivation tool particularly applied to verbs. However, the Spanish infix has been morphologically ignored, if not mistaken with the interfix or the suffix. Against this general trend of thought, reflected in the existing literature, the author has developed arguments for the acceptance of the infix in Spanish. Space limitations recommend concentrating the efforts of the present study only on the -iz- Spanish causative infix, generally misinterpreted as suffix. Since -iz- is often placed inside the base of an original verb, between the root and the thematic vowel, its nature will be fundamental to determine the morphological value granted to the -iz- affix. Consequently a thorough analysis of the verbal thematic vowel is required within this paper to complete the theoretical analysis for the existence of the causative infixation in Spanish.